Facebook levels the playing field: Dyslexic students learning through digital literacies - Owen Barden (Research in Learning Technology, 2014)
Dyslexia has an ambivalent relationship with learning technology. Any potential gains may be nullified if the technology is perceived to exacerbate stigma. This paper examines the use of an ‘everyday’ technology, Facebook, by a small group of sixth form students labelled as dyslexic. ‘Levelling the playing field’ is a phrase the participants used often when discussing what they wanted from learning technology. Because dyslexia usually is defined in terms of significant difficulties with literacy, we might reasonably anticipate that the participants would see Facebook as stigmatising rather than levelling the playing field, because of the very public literacy events that it demands. However, the data indicate that far from shying away from Facebook because of fear of their difficulties with literacy being exposed, the participants enthusiastically embraced it. The students saw Facebook as a desirable presence in their education, one that supported inclusion. For them, levelling the playing field with Facebook had five dimensions: keeping up to date and meeting deadlines; increased control over learning; developing metacognitive awareness; greater control over literacy process and demands; and being experts and helpers. The findings perhaps challenge some assumptions about dyslexia, literacy and learning, and may be of interest to teachers working with dyslexic students, or researchers studying learning in digitally mediated social networks.